Efficacy of Omega-3, -6, and -9 Fatty Acids, Alone or in Combination With Low Dose Aspirin, in Improvement of Uterine Blood Flow in Women With History of Recurrent Miscarriage: A Prospective, Randomized, Clinical Trial - Shahram Ala; Sepideh Payvandi; Maryam Barzin; Mahdieh Tavajoh; Hamidreza Samaei (Mazandaran University of Medical Sciences, 2022)
Background: Much evidence suggests that increased uterine blood flow resistance (reduced uterine perfusion) raises the risk of Recurrent Miscarriage (RM).  Objectives: This study aimed at evaluating the efficacy of omega-3, -6, and -9 fatty acids, alone or in combination with aspirin, in reducing uterine blood flow resistance in women with a history of RM. Methods: A total of 45 women with a history of two or more miscarriages and increased uterine artery blood flow resistance were included in this randomized clinical trial. They were randomly assigned to aspirin (80 mg/d) (group A, n=15), omega-3, -6, and -9 fatty acids (4800 mg/d) (group O, n=15), or combination therapy (group AO, n=15). The patients were visited after two months, and the uterine artery blood flow resistance was measured by Doppler sonography. Results: The Mean±SD age of participants was 32±3.5 years in group A, 32±3 years in group O, and 32.4±3 years in group AO. There was no significant difference between three groups in age (P=0.7), duration of marriage (P=0.55), duration of infertility (P=0.43) and number of previous miscarriages (P= 0.51). In all three groups, after two months of treatment, the average uterine artery blood flow resistance reduced considerably compared with the beginning of the trial (P=0.0001); however, there was no significant difference between the three groups (P=0.56).  Conclusion: According to the study results, omega-3, -6, and -9 fatty acids can reduce uterine artery blood flow resistance and improve the uterine blood flow in women with RM, with equal efficacy to aspirin. Also, combination therapy offers no advantages over monotherapy.